A Phase I Study of Abiraterone Acetate Combined with BEZ235, a Dual PI3K/mTOR Inhibitor, in Metastatic Castration Resistant Prostate Cancer. (May 2017) - Wei, Xiao X.; Hsieh, Andrew C.; Kim, Won; Friedlander, Terence; Lin, Amy M.; Louttit, Mirela; Ryan, Charles J.
Abstract: Lessons Learned: The combination of standard dose abiraterone acetate and BEZ235, a pan‐class I PI3K and mTORC1/2 inhibitor, was poorly tolerated in men with progressive mCRPC. Although the clinical development of BEZ235 has been discontinued in prostate cancer, agents that more selectively target PI3K‐AKT‐mTOR signaling may have a more favorable therapeutic index and should continue to be explored. Background: Androgen receptor (AR) and phosphatidylinositol‐3 kinase (PI3K) signaling are two commonly perturbed pathways in prostate cancer. Preclinical data have shown that the two pathways compensate for each other when one is inhibited, and combined inhibition of AR and PI3K signaling may be a viable strategy to prevent or overcome castration resistance. Methods: This phase I study evaluated the safety and tolerability of abiraterone acetate and prednisone combined with BEZ235, a dual PI3K and mTORC1/2 inhibitor, in men with progressive metastatic castration resistant prostate cancer (mCRPC) who have not received prior chemotherapy. Results: Six patients ( n = 6) were treated at the starting dose level of abiraterone acetate 1, 000 mg with prednisone 5 mg twice daily and BEZ235 200 mg twice daily in a 3 + 3 dose escalation design. The study was terminated early because three of the six patients (50%) experienced dose‐limiting toxicities: grade 3 mucositis, grade 3 hypotension, and grade 4 dyspnea and pneumonitis. All six patients had previously progressed on abiraterone/prednisone. The median treatment duration was 27 days (range: 3–130 days). No prostate‐specific antigen (PSA) decline or objective response were observed. Conclusion: The combination of standard‐dose abiraterone/prednisone with BEZ235 200 mg twice daily was poorly tolerated in patients with mCRPC. The on‐target and off‐target effects of dual PI3K and mTORC inhibition likely contributed to the unacceptable toxicity profile. The Oncologist 2017;22:503–e43